Strain rate effect on the mechanical response of duplex stainless steel - Ameri, A.; Escobedo-Diaz, J.; Quadir, Md Zakaria; Ashraf, M.; Hutchison, W. (2018)
© 2018 Author(s). The effect of strain rate on the mechanical response and microstructural evolution of Lean Duplex Stainless Steel 2101 (LDSS 2101) has been investigated. The compressive response of LDSS 2101 at different strain rates was measured by using a universal testing machine and Split Hopkinson Pressure Bar (SHPB). The microstructural changes were examined using optical microscopy, electron microscopy and Electron Backscatter Diffraction (EBSD). The results showed that the mechanical response of LDSS 2101 depends on strain rate. Microstructural observations revealed that some of the austenite phase transforms to martensite. The volume fraction of the martensitic phase, which influences the mechanical response, increases with increasing plastic strain but decreases with increasing strain rate.